The Relationship Between Knowledge and Regularity of Antenatal Care Visits During The Covid-19 Pandemic - Yuni Retnowati (International Journal of Health and Pharmaceutical (IJHP), 2022)
Antenatal care (ANC) purpose to obtaining a safe and positive pregnancy and childbirth. Covid-19 pandemic bring an impact on the health sector, including ANC visits. This study purpose to analyze the relationship between knowledge with regularity of ANC visits for pregnant women in the third trimester during the Covid-19 pandemic in the work area of UPTD Puskesmas Karang Rejo. This research is a correlative analytical study with cross-sectional approach. The population were all pregnant women in third trimesters who did ANC with samples 37 respondents. The sampling technique was consecutive sampling. Data analysis using Spearman Rho statistical test. The result of bivariate analysis was p =0,001, and the coefficient value (r = 0,744) meaning there is a correlation between the knowledge and the regularity of ANC visit. Pregnant women are expected to always open mind to receiving the information that given by health workers to increase their knowledge about ANC visits so support and motivate to did ANC visit regularly.